Práticas curriculares da educação física na educação infantil : um estudo de caso - Nunes, Kezia Rodrigues (2007)
The work is about the study of the Physical Education concerning Children’s Education curriculum, highlighting, giving value and a new meaning, with the school subjects, the knowledge-production. Its investigative locus is the Municipal Center of Children’s Education of Vitória/ES that is engaged with the collective construction of possibilities of education and care of children under six years old through the discussion of the Political-Pedagogical Project. As instruments of data collection, it uses the documental analysis, semi-structured interview, focal group, participant observation, photographical records and journal field. It investigates the spaces of a collective discussion, the documents systematization, the proposals and institution actions, as well as the comprehension of the Technical-Pedagogical Board (CTA) and the teachers related to the curriculum’s objectivities and the collaborative relations of the work. The findings indicate the presence of Physical education as a nonstop way in the institution, in the last 16 years, although records of teachers or of CTA were not found about such pedagogical practice. It also points the existence of two interpretative communities, of regent and specialist teachers, because of a certain resistance in guarantying spaces of discussion and collaborative actions. About the pedagogical practice of the Physical Education, it analyses, discusses, investigates and interferes with teachers about the possibilities of work that value the school community knowledge. It identifies changes in the methodological organization of the classroom, in the evaluation and relation with children. Finally, it proposes an organization for the Children’s Education work that, even keeping the disciplinary format, wants to be materialized in a non-disciplinary format, in order not to promote a specialization in the pedagogical practice with little kids.